Effects of rocuronium, sugammadex and rocuronium-sugammadex complex on coagulation in rats - Cavalcanti,Ismar Lima (2020)
Abstract Background and objectives: Sugammadex is an alternative pharmacological drug capable of reversing neuromuscular blockades without the limitations that are presented by anticholinesterase drugs. Coagulation disorders that are related to treatment with sugammadex were reported. The exact mechanism of the effects on coagulation are not fully understood. The objective of this research is to evaluate the effects of rocuronium, sugammadex and the rocuronium-sugammadex complex on coagulation in an experimental model in rats. Methods: This is an experimental randomized animal study. Wistar rats were randomly assigned into the following groups: the Control Group; the Ssal Group - 0.5 mL of intravenous saline; the Sugammadex Group - intravenous sugammadex (100 mg kg−1); and the Rocuronium-Sugammadex Group - intravenous solution with rocuronium (3.75 mg kg−1) and sugammadex (100 mg kg−1). Anesthesia was performed by using isoflurane with controlled ventilation. Coagulation factors were measured 10 minutes after the end of the preoperative preparation and 30 minutes after the administration of the drugs in accordance with the chosen groups. Results: Platelet counts, prothrombin times, and activated partial thromboplastin times were similar between the groups and between the moments within each group. There were reductions in the plasma fibrinogen levels between sample times 1 and 2 in the Rocuronium-Sugammadex group (p = 0.035). Conclusions: The rocuronium-sugammadex complex promoted reductions in plasma fibrinogen counts, although the levels were still within normal limits.